2014
DOI: 10.1158/1535-7163.mct-13-0378
|View full text |Cite
|
Sign up to set email alerts
|

Embelin Reduces Colitis-Associated Tumorigenesis through Limiting IL-6/STAT3 Signaling

Abstract: The interleukin-6 (IL-6)/STAT3 signaling regulates survival and proliferation of intestinal epithelial cells and plays an important role in the pathogenesis of inflammatory bowel disease and colorectal cancer. Embelin is a small molecule inhibitor of X-linked inhibitor of apoptosis protein (XIAP), with antioxidant, anti-inflammatory, and antitumor activities. We previously showed that embelin inhibits the growth of colon cancer cells in vitro, and effectively suppresses 1,2-dimethylhydrazine dihydrochloride-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 46 publications
(66 reference statements)
4
51
0
2
Order By: Relevance
“…Our previous research found that embelin suppresses dendritic cell functions and limits autoimmune encephalomyelitis through the TGF-beta/beta-catenin and STAT3 signaling pathways [11], and embelin reduces colitis-associated tumorigenesis through limiting IL-6/STAT3 signaling [12]. Meanwhile, the mechanisms that embelin directly inhibited the infiltration of inflammatory cells, Th1, Th2, Th17, MDSC, Treg, and the secretion of inflammatory cytokines, IL-4, IL-17A, GM-CSF, IL-1β in pancreatic cancer need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research found that embelin suppresses dendritic cell functions and limits autoimmune encephalomyelitis through the TGF-beta/beta-catenin and STAT3 signaling pathways [11], and embelin reduces colitis-associated tumorigenesis through limiting IL-6/STAT3 signaling [12]. Meanwhile, the mechanisms that embelin directly inhibited the infiltration of inflammatory cells, Th1, Th2, Th17, MDSC, Treg, and the secretion of inflammatory cytokines, IL-4, IL-17A, GM-CSF, IL-1β in pancreatic cancer need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research found that embelin could limit autoimmune encephalomyelitis [11] and reduce colitis-associated tumorigenesis [12] by blocking the expression of the Th17 cell-polarizing cytokines IL-6 and consequently the polarization of Th17. These results implied that embelin may exert anti-inflammatory effect by restricting the production of IL-6 in tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…First advances were achieved on experimental models. So, IL-6/STAT3 signal way blocking resulted in a significant decrease of tumor incidence on a murine model associated with chronic colitis oncogenesis [96]. Another trial on a similar model of induced oncogenesis showed the blocking of granulocyte colony stimulating factor (G-CSF) activating growth and migration in colorectal carcinoma culture cells that resulted in reduced incidence of tumor and immune response enhancement [97].…”
Section: Application Of Cytokines In Colon Cancer Immunotherapymentioning
confidence: 99%
“…Embelin (2,5-dihydroxy-3-undecyl-1,4-benzoquinone), a phytochemical isolated from Embelia ribes [1], has antihelminthic [2], contraceptive [2], anti-inflammatory [3][4][5][6] and anticancer [1][2][3][4][6][7][8][9][10][11] potency, as well as photosensitizing [1] and radiation sensitizing [12] property. Embelin has further been shown to decrease cardiac injury following experimental myocardial infarction [13] and to protect cells against UVB-induced oxidative damage [14], but to aggravate the encephalopathy following neonatal hypoxia-ischemia [15].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms mediating the effects of embelin include mitochondrial depolarization [22,23,27,29,31], induction of oxidative stress [17], inhibition of X-linked inhibitor of the apoptosis protein (XIAP) [3,5,10,11,16,19,20,24,30,[32][33][34][35][36], of PTEN/ Akt/mTOR/S6K1 signaling [37,38] and of the transcription factors NF-κB [2,11,16,25,39] and STAT3 [3,6,18,37], increase of intracellular free Ca 2+ concentration ([Ca 2+ ] i ) [40], upregulation of TRAIL receptors DR4/DR5 [19] and Bax [7,23,31], as well as activation of p38 kinase [17,32], Jun kinase [17], p53 transcription factor [6,22,28,32] and caspases [7,8,11,…”
Section: Introductionmentioning
confidence: 99%